Sustainable Energy for All 2015 : Progress Toward Sustainable Energy - World Bank; International Energy Agency (Washington, DC: World Bank, 2015)
Sustainable Energy for All seeks to improve the lives of billions of people across the world and ensure a more sustainable future by working to achieve its three global objectives: universal access to energy; doubling of the rate of improvement in energy efficiency; and doubling of the share of renewable energy in the global energy mix. Accountability and transparency are essential for tracking Sustainable Energy for All’s global progress. Doing so will clarify where the initiative stands, how various actions are contributing to the three objectives, how much remains to be accomplished, and where more action is needed to achieve Sustainable Energy For All. This second edition of the SE4ALL Global Tracking Framework provides an update of how the world has been moving towards the three objectives over the period 2010-2012. The report also explores a number of complementary themes. First, it provides further analysis of the financial cost of meeting the SE4ALL objectives as well as the geographical and technological distribution of the investments that need to be made. Second, it explores the extent to which countries around the world have access to the technology needed to make progress towards the three goals. Third, it identifies the improvements in data collection methodologies and capacity building that will be needed to provide a more nuanced and accurate picture of progress over time. Finally, this new edition of the Global Tracking Framework explores and introduces nexus concepts focusing on the links between energy and four priority areas of development: food, water, human health, and gender. Links between most of these areas and energy are well established, but often presented in isolation of each other.